Adjunct psychomotor trauma exposure in the treatment of post-traumatic stress disorder: a case series - Claire Guépin; Stéphane Duhem; Nicolas Gaud; Frédérique Warembourg; Guillaume Vaiva; Arnaud Leroy (European Journal of Psychotraumatology)
Introduction: Psychotraumatic disorders, particularly post-traumatic stress disorder (PTSD), have been a major public health issue for many years. However, many patients remain resistant to treatment, with significant levels of residual symptoms, a high dropout rate, and poor functional prognosis despite a reduction in psychotraumatic symptoms. The physical impact of trauma might influence treatment response. We have developed an integrative method for patients suffering from post-traumatic stress disorder (PTSD). In this study, we report the cases of 16 successive patients with PTSD treated with adjunct psychomotor trauma exposure.Methods: The data were collected retrospectively from the clinical records of subjects treated with adjunct psychomotor exposure therapy at the Hauts-de-France Regional Center for Psychotrauma. Severity of psychotrauma was reported using PCL-5 before and one month after treatment.Results: A decrease in PCL-5 score was seen in all participants between baseline (45.6 ± 11.6) at the end of treatment (16.6 ± 10.1) (p < .001).Conclusion: Adjunct psychomotor exposure therapy is a promising tool for the treatment of PTSD. Future high-quality randomised controlled trials are necessary.